The effects of social isolation on gait parameters of older people with Parkinson's disease - Sirico, Thiago Martins [UNESP] (Universidade Estadual Paulista (Unesp), 2023)
The COVID-19 disease acquired pandemic proportions in 2020. To deal with the scenario, social isolation (SI) was adopted, which configures a lack of contact with people and places. The impediments of this measure, however, can bring risks to older people with Parkinson's disease (PD), such as impairments in gait parameters. Therefore, the aim of this study was to verify the effects of SI on gait parameters in people with Parkinson's disease. Thirty-three people with PD were recruited. Gait assessment was conducted in two periods: February 2020 and March 2022 (before and after the SI, respectively). For that, participants were invited to walk on a 5.74m mat with pressure sensors under two conditions: preferred walking speed and fast walking speed. Three trials were performed for each condition. The gait parameters analyzed were stride length, stride time, double support time, stride velocity, stride width, and cadence. Statistical analysis was performed by paired t-tests for the comparison of gait parameters between moments (pre and post-SI). In the preferred walking speed condition, the participants reduced their stride length (t15 = 3.88, p = 0.001) and stride velocity (t15 = 3.63, p = 0.002) in the post-si period. in the fast-walking speed condition, the participants also reduced their stride length (t15 = 3.73, p = 0.002) and stride velocity (t15 = 2.86, p = 0.012) in the post-SI period. Therefore, the SI period caused by the COVID-19 pandemic negatively affected the mobility of people with PD, reducing stride length and stride velocity.

A COVID-19 adquiriu proporções pandêmicas em 2020. Para lidar com tal cenário, o isolamento social (IS), que configura uma perda de contato com pessoas e lugares, foi adotado. Contudo, os impedimentos causados por esta medida podem trazer riscos para idosos com doença de Parkinson (PD), como déficits nos parâmetros do andar. Assim, o objetivo deste estudo foi verificar os efeitos do IS nos parâmetros do andar de idosos com doença de Parkinson. Trinta e três pessoas com PD foram recrutadas. A avaliação do andar aconteceu em dois períodos: Fevereiro de 2020 e Março de 2022 (antes e depois do IS, respectivamente). Para isso, os participantes foram convidados a caminhar sobre tapete de 5.74m, com sensores de pressão, em duas condições: velocidade preferida e velocidade rápida. Três tentativas foram realizadas para cada condição. Os parâmetros do andar analisados foram comprimento da passada, tempo da passada, tempo em duplo suporte, velocidade da passada, largura da passada e cadência. A análise estatística foi realizada por meio de testes t pareados para a comparação dos parâmetros do andar (pré e pós IS). Na condição andar em velocidade preferida, os participantes reduziram o comprimento (t15 = 3,88, p = 0,001) e a velocidade da passada (t15 = 3,63, p = 0,002) no período pós IS comparado ao pré. Na condição andar em velocidade rápida, os participantes também reduziram o comprimento (t15 = 3,73, p = 0,002) e a velocidade da passada (t15 = 2,86, p = 0,012) no período pós IS comparado ao pré. Portanto, o período de IS causado pela pandemia de COVID-19 afetou negativamente a mobilidade das pessoas com DP, reduzindo o comprimento e a velocidade da passada.
Os efeitos do isolamento social nos parâmetros do andar de idosos com doença de Parkinson
Keywords: Walking; COVID-19; Neurodegenerative disease; Andar; Doença neurodegenerativa